Analisis Faktor Penyebab Perambahan di Cagar Alam Wolo Tadho (Studi Kasus Desa Latung dan Desa Tadho Kecamatan Riung, Kabupaten Ngada, Provinsi Nusa Tenggara Timur) - Yeremias Tanik; Maria M. E. Purnama; Norman P. L. B. Riwu Kaho; Roni Haposan Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Encroachment is one of the problems that occured in the Wolo Tadho Nature Reserve. This study aims to determined several factors that caused encroachment in the Wolo Tadho Nature Reserve and activities in overcoming the problem. The method used in this study was a non-probabity sampling method for community people that lives nearby the research area and the management of the Wolo Tadho Nature Reserve. The sampling techniques for the community people uses the snowball sampling method, while for the management officer of the Nature Reserve uses the purposive sampling method. The results showed that there were eight factors causing encroachment in the Wolo Tadho Nature Reserve, namely economic, education, number of family members, limited of land, unclear boundaries area, community awareness, land tenure, and limited of officer number. Activities carried out in overcoming this encroachment problem are patrolling the area, joint patrols with the police, forming forest police (POLHUT) in partnership with the Communities, socialization to the community about the Wolo Tadho Nature Reserve Area, collaboration with the government in maintaining the Nature Reserve and to overcomes the problems of enchroachment, assistance and training to the community in optimizing agricultural products and the approaches through a 3-pillar scheme involving government, community, and indigenous leaders as well as religious leaders.